(untitled) (Journal of Environmental Science and Natural Resources, 2013)
A study was conducted to evaluate level of water pollution and its influence on heavy metal contaminations of lake water of Dhaka metropolitan city. The water samples were collected from lakes of Dhaka metropolitan city during February to March, 2008. The chemical analysis of water samples included pH, EC, As, Cu, Mn, ’ln. Pb and Cd. Analysis of lake water samples was done at the Central Laboratory of Bangladesh Agricultural University, Mymensingh. The concentrations of heavy metal of lake water were recorded as: in case of pH = 6.95, in case of EC = 22.44 (?scm-1), in case of Cu = 0.018 ppm, in case of Zn = 0.274 ppm, in case of Mn = 0.084 ppm, in case of As = 0.002 ppb, in case of Pb = 0.002 ppm and in case of Cd = 0.044 ppm. The pH value of lakes water range from 5.34 to 7.68, an indication of slightly acidic to alkaline in nature. The average EC value for lakes water ranged from 17.61 to 34.61 ?Scm-1 where EC value varied from 14.24 to 33.48 ?Scm-1 in the lake water. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14841 J. Environ. Sci. & Natural Resources, 5(2): 345-348 2012